Caspofungin in pediatric patients. Issue 6 (December 2008) - Lehrnbecher, Thomas; Groll, Andreas H
Invasive fungal infections have emerged as one of the most significant complications in severely immunocompromised pediatric patients, such as children suffering from hematological malignancies or children undergoing hematopoietic stem cell transplantation. In addition, neonates, in particular preterm infants, are at risk for invasive mycoses. Owing to the development of new generations and new classes of antifungal compounds, the antimycotic armamentarium has considerably expanded over the last few years. Caspofungin is the first licensed compound of the novel class of echinocandin lipopeptides. This article reviews the published data on the experience with caspofungin in neonates and immunocompromised children.